The Role of Organizational Culture in the Emergence of Teachers' Professional Ethics - Ali Asgari; Sajjad Bahmani (National Research Mordova State University, 2022)
Introduction. Paying attention to the improvement of teachers' professional ethics is of special importance in educational organizations, especially secondary schools. Accordingly, the present study seeks to investigate the role of organizational culture in the emergence of teachers' professional ethics. Materials and Methods. This research is descriptive-correlational in terms of data collection method. The statistical population of the study includes all teachers in Khosf, 180 people, of which according to Cochran's formula, 123 people were selected as sample members by simple random sampling. Respondents included a majority of female. Denison's Organizational Culture Questionnaire and Cadozier Professional Ethics Questionnaire were used to collect data. The validity of the questionnaires was confirmed using content validity and their reliability was obtained by Cronbachʼs alpha of 0.97 and 0.94, respectively. Data analysis was performed in SmartPLS 3 software environment using structural equation modeling method. Results. The results of testing the main hypothesis of the research showed that organizational culture plays a role in the development of teachers "professional ethics and about 94% of changes in teachers" professional ethics in schools are explained by organizational culture. Also, the results of testing the sub-hypotheses of the research based on examining the role of each component of organizational culture in the emergence of teachers' professional ethics showed that each of the components of work engagement, integration, adaptation and mission explain the changes in the professional ethics of teachers in schools, among which, the mission component has the most and compatibility has the least impact. Discussion and Conclusion. The conclusions contribute to the development of the concept of organizational culture, provided that organizational culture and its components play a critical role in the development of teachers' professional ethics. Accordingly, it can be concluded that a good organizational culture in schools can strengthen the professional ethics of teachers and create a good environment for the emergence of professional ethics among them.